Dual fungal infection with Lomentospora prolificans and Aspergillus fumigatus: A pathogenetic diagnosis elucidated after two decades by sequential examinations - Yoshitsugu Sugiura; Naoshi Sugimoto; Takayuki Takahashi; Tadahiko Matsumoto (Clinical Case Reports, 2021)
Abstract A 44‐year‐old male Japanese was admitted for further post‐remission treatments for acute myeloid leukemia. He developed a right orbital abscess. An isolate of Lomentospora prolificans was obtained from the lesion, and orbital biopsy also revealed the presence of Aspergillus fumigatus. This fatal case involved a concurrent dual fungal infection.